2019
DOI: 10.1002/ijc.32053
|View full text |Cite
|
Sign up to set email alerts
|

Cancer incidence in Northern Uganda (2013–2016)

Abstract: Gulu Cancer Registry was established in 2014 to assess the incidence and survival of cancer in 4 districts of the Acholi Sub‐region of northern Uganda. Here we report the results of the first 4 years of registration (2013–2016) in this largely rural population of 771,514. In total there were 1627 cases of cancers registered; 644 among men (corresponding to an ASR of 106.7 per 100,000 population) and 983 cancer cases among women (ASR 118.5 per 100,000). The most common cancers were cancers of the cervix and non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 8 publications
2
16
0
Order By: Relevance
“…Low utilization of prostate cancer screening have been associated with poor knowledge about prostate cancer and the screening methods in black populations in America and Africa [10, 15, 19, 23, 24]. It is well known that low utilization of prostate screening services contributes to late diagnosis and increased mortality and morbidity related to prostate cancer [1, 4, 5, 25]. Overscreening has potential to cause harm through overdiagnosis and unnessesary invasive procedures, hence its critical that men should be subjected to physical screening based on risk age and having suggestive symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Low utilization of prostate cancer screening have been associated with poor knowledge about prostate cancer and the screening methods in black populations in America and Africa [10, 15, 19, 23, 24]. It is well known that low utilization of prostate screening services contributes to late diagnosis and increased mortality and morbidity related to prostate cancer [1, 4, 5, 25]. Overscreening has potential to cause harm through overdiagnosis and unnessesary invasive procedures, hence its critical that men should be subjected to physical screening based on risk age and having suggestive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Prostate cancer is an adenocarcinoma of the male prostate and is one of the most common cancers in the world and a leading cause of cancer related deaths among men globally [13]. While prostate cancer is thus an important health burden among men across the globe, the highest incidence rates are found in sub-Saharan Africa [1, 2, 4, 5]. A systematic review of prostate cancer in Africa estimated an overall continent-wide pooled incidence rate of 21.95/100,000 population [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerns are increasing that young adults (particularly young men) in the North are presenting to care with advance liver cancer and experiencing rapid progression to death. This is affirmed by recent evidence documenting liver cancer incidence of 12.8 (men) and 6.9 (women) per 100,000 population between 2013–2016 in the Northern region, which is higher than Kampala in Central Uganda as well as most sub-Saharan African countries [ 15 ]. The seemingly ‘sudden’ onset of symptoms and rapid decline in one’s health may be contributing to emergence of stigmas similar to those related to infectious diseases such as ebola and HIV [ 16 ].…”
Section: Introductionmentioning
confidence: 88%
“…The authors found that although there was a high prevalence of breast cancer in Northern Uganda compared to the rest of the country [24,25], the level of awareness and practices regarding downstaging activities were low/limited. Most participants with the highest quali cation (university degrees) had worked in the Gulu main market for 1-10 years, and vendors had statistically signi cant associations with downstaging awareness and practices (Table 1, Table 2, Table 3, Table 4, Table 5, Table 6, Table 7, Table 8).…”
Section: Sociodemographic Characteristics and Awareness Of Breast Cancer Downstaging Practicesmentioning
confidence: 99%